The effect of the Appleton model on learning to perform the long jump for first-year students in the College of Basic Education - Ghaidan , Russul (Journal of Physical Education, 2025)
The research has been conducted to prepare educational units according to the Appleton model for teaching the skill of long jump to first-stage students and identify its effect on learning. The researcher used the comparative quasi-experimental design with pre-test and post-test for control group and experimental group. Population This study population consists of (115) first-stage students from the Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriya University, for the academic year 2023–2024 distributed on six divisions: (A–F). Two divisions were chosen by lottery: Division (B) an experimental group and Division (E) control group, 25 students in each division (total 50, which accounts for 43.47% of the population). Experimental subjects learn the long jump according to Appletons model, while control subjects learn it in accordance with the traditional imperative method used in the curriculum. After implementing pre- and post-tests with statistical analyses it was found that the Appleton model did have a significant impact on learning the long jump by increasing motivation via excitement, competition and engagement which facilitated the experience of easier and effective learning. Based on the significance of the Appleton approach in meeting educational aims and performance levels for long jump and other sports skills at various age and educational stages, the most important suggestion arising from this study is to include Appleton model in teaching long jump or other sports skills.